PENGARUH KOMITMEN PROFESIONAL MULTI DIMENSI TERHADAP PERILAKU UNDERREPORTING OF TIME (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK SECOND TIERS DI INDONESIA) - sri wahyuni (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The purpose of this study is to determine the commitment of professional affective, professional commitment continuance, normative professional commitment to underreporting of time behavior. The population in this study is the auditor at Public Accounting Firm second tiers in Indonesia. Collection of sample of 70 people. Data processing is done by structural equation modeling analysis using WarpPLS 5.0 software. The results show that professional commitment has a positive effect on underreporting of time behavior. This indicates that the higher the professional auditor's commitment, the better the auditor handles the underreporting of time behavior, and the lower the auditor's professional commitment, the lower the ability to handle underreporting of time behavior.Keywords: Professional Affective Commitment, Continuance Professional Commitment, Normative Professional Commitment, Underreporting Of Time Behavior